Individual and community-level determinants of neonatal mortality in Somalia: a multilevel analysis of the 2018–2019 demographic and health survey - Kahie, Awo Mohamed; Ali, Abdirahman Omer; Omer, Nura Mohamed; Kahie, Suhaib Mohamed; Nadarajah, Saralees; Omer, Nima Muhammad (Frontiers in Pediatrics, 2025)
BackgroundSomalia faces one of the world's highest neonatal mortality (NM) rates, representing a severe public health crisis. This study aimed to identify the individual and community-level determinants of NM and describe its geographic distribution in this fragile setting, using data from the 2018–2019 Somali Demographic and Health Survey (SDHS).MethodsThis cross-sectional study analyzed a weighted sample of 7,519 live births from the 2018–2019 SDHS. A two-level multilevel logistic regression model was used to identify individual and community-level determinants of neonatal mortality and to assess regional variations.ResultsThe neonatal mortality rate (NMR) was 34.1 deaths per 1,000 live births. At the individual level, multiple births significantly increased the odds of death [Adjusted Odds Ratio (AOR) = 3.92; 95% CI: 2.35–6.56], while a preceding birth interval of ≥2 years was protective, reducing mortality odds by 50% (AOR = 0.50; 95% CI: 0.39–0.66). Female newborns had 26% lower odds of mortality than males (AOR = 0.74; 95% CI: 0.58–0.95). At the community level, home delivery was a major risk factor, increasing the odds of neonatal death by over 50% compared to facility-based delivery (AOR = 1.52; 95% CI: 1.04–2.22). The analysis also revealed significant geographic disparities, with some regions showing substantially lower mortality risk than others, notably Hiraan (AOR = 0.15) and Banadir (AOR = 0.23) compared to Awdal.ConclusionNeonatal mortality in Somalia is alarmingly high and inequitably distributed, driven by a combination of biological risks, healthcare access failures, and regional disparities. Interventions must prioritize increasing access to and utilization of health facilities for childbirth, strengthening family planning services to promote healthy birth spacing, and enhancing specialized care for high-risk newborns, particularly in regions identified with the highest mortality burden. These targeted strategies are essential to reduce preventable newborn deaths in Somalia.